Supply-chain risk mitigation with integration of House of Risk and fuzzy logic: A case study in bakery industry - Maria Ulfah; Putro Ferro Ferdinant; Dyah Lintang Trenggonowati; Missela Salsabila (Journal Industrial Servicess, 2022)
IKM Bread is a food industry located in Cilegon producing bread. IKM Bread has a supply chain system from raw material procurement, production process activities, packaging, shipping, and marketing to the hands of consumers. In its supply chain, IKM Bread has several risks that are happening, and that may occur, such as production planning, production process, and distribution. Therefore, risk identification and mitigation activity are required to minimize risk. This research aims to identify the supply chain in IKM Bread, analyze and be involved in the supply chain at IKM Bread and determine the mitigation strategy prioritized in supply risk management in the bakery industry in IKM Bread. The method used is SCOR and HOR phase 1 integrated with Fuzzy Logic to find potential risks. Then, HOR phase 2 methods are used to find the appropriate mitigation proposals for these potential risks. Based on the research, IKM Bread has 32 risk events and 20 risk agents. Therefore, the proposed risk mitigation consists of 15 proactive actions, which include conducting training for all employees, evaluating after production, briefing before starting production, and making backup production plans.